The zero risk fallacy? Banks' sovereign exposure and sovereign risk spillovers - Karolin Kirschenmann; Josef Korte; Sascha Steffen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
European banks are exposed to a substantial amount of risky sovereign debt. The "missing bank capital" resulting from the zero-risk weight exemption for European banks for European sovereign debt amplifies the co-movement between sovereign CDS spreads and facilitates cross-border financial-crisis spillovers. Risks spill over from risky periphery sovereigns to safer core countries, but not in the opposite direction nor for exposures to countries not exempted from risk-weighting. We consider the trade-off of benefits of sovereign debt (for banks and sovereigns) and spillover risk when applying risk-weights. More bank capital as well as positive risk-weighting for sovereign exposures mitigates spillovers.
urn:nbn:de:bsz:180-madoc-438874
Keywords: G01; G21; G28; G14; G15; F23; 330; sovereign debt; sovereign risk; bank risk; CDS; contagion; zero risk weight; Basel III; CRD; EBA capital exercise